A Creative Dance Learning Model: Improving Interpersonal Intelligence of Early Childhood - Yetti, Elindra (International Journal of Engineering and Technology, 2018)
Creative dance learning is an activity that emphasizes the creativity of children motion through the expression of free movement based on the imagination of children. This study discusses the creative dance learning model to improve Early Childhoodâ€™s interpersonal intelligence. Interpersonal intelligence is the ability to understand and deal with the attitudes and feelings of others that characterized by sociability, socializing, and empathy. A research method used was quasi-experimental research. It conducted on students of group B Kindergarten in East Jakarta. The result revealed that tcount value is 9.58 and ttable value is 2.083. H0 is rejected and Ha is accepted. Thus, 1â‰ Â 2, the pre-test value is not equal to the post-test value. In brief, it can improve the interpersonal intelligence of Early Childhood students. A creative dance learning model activities conducted through the exploration and improvisation of children's movements in groups. It worked together to move the motion into the form of motion of dance. It also has an impact on the interaction between Early Childhood students in the group. In conclusion, the experience of working together and interacting can improve Early Childhood studentsâ€™ interpersonal intelligence.Â Â